Customer Perception towards Online Shopping - Agarwal, Varsha (JETIR, 2022)
The conventional methods of people shopping and purchasing products and services have been altered by the internet. Going digital is the current trend in this day and period of fast change. To stay competitive, every physical store is now attempting to have an online presence. Customers utilize the internet for more than just online shopping; they also use it to compare costs, product features, and post-purchase support options. Online shopping, commonly referred to as e-shopping, is a type of electronic commerce that enables customers to make direct purchases from sellers using a computer browser and the Internet. This research study's major goal is to evaluate and investigate customer perceptions about internet buying. The quantitative technique was employed in the current research article to examine customer preferences for internet purchasing.
Keywords: Consumer behaviour; Impulsive buying; Personality; Materialism; E-commerce retailing; Mobile apps; Ease of use